PHARMACOECONOMIC ANALYSIS AND PRESCRIBING PATTERNS OF PATIENTS SUFFERING FROM ASTHMA IN A TERTIARY CARE HOSPITAL - T. Pavithra; Abdul Haseeb TS; T. Naga Aparna; Rohit kumar; Konda Shravan Kumar; Jaffer sadik (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Asthma is the most common respiratory disease, but the information regarding the Pharmacoeconomics of this disease isn’t widely available. Pharmacoeconomics involves the study of medication-related costs in the prescription, diagnosis, and treatment of the disease. It also includes the study of the effects of these medication costs on the financial status of the patients. This helps in the reduction of medication-related costs. The present study was conducted to perform “Pharmacoeconomic Analysis and to study the prescribing patterns in patients suffering from Asthma in BBR Multispecialty Hospital, Balnagar, Hyderabad over a period of 3 months i.e., from December 2021 to February 2022. The primary objective was to perform pharmacoeconomic analysis in asthma patients. The secondary objective was to study the prescription patterns of asthma medication in a tertiary care hospital. This is a consecutive consent, purposive study conducted at BBR Multispecialty Hospital carried out for a period of 3 months from December 2021 to February 2022. All the patients meeting the inclusion and exclusion criteria were informed the details of the study, and consent were obtained. About 110 patients within the age group of 15-70 were collected. The suitable statistical analysis with Microsoft excels was done. The average cost per day of asthma was found to be 79 rupees for mild asthma patients, 432 rupees for moderate asthma patients, and 2161 rupees for severe asthma patients. Among these, the highest cost was found to be 120.4 rupees for Nebulizer Foracort and the least cost was found to be 9.04 rupees for Inhaler Airz FB. The overall healthcare costs can be reduced by evaluation and reassessment of pharmacoeconomic data from manufacturing to dispensing